Digital Currency and its Implementation in Uzbekistan - Anvar Khudoyshukurovich Khurramov (Academia One Publishing, 2023)
Money is one of the greatest inventions of mankind. There are many definitions of money that characterize the essence of money, which basically leads to the fact that money is a universal equivalent, with its help determined measure of value - the price of other goods. The development of information technology has led to the fact that in the digital economy, countries gradually began to introduce digital currencies into circulation. In this article briefly discusses the essence and models of digital money, as well as the implementation of digital currency in Uzbekistan.
Keywords: Money; cash; non-cash money